Encontros entre dança, subjetivação e saúde mental - Liberato, Mariana Tavares Cavalcanti (2007)
Taking from starting point the contact with the experience of a dancing body language group at Centro de Atenção Psicossocial (CAPS) II in Fortaleza-CE, aiming to investigate the relationship between what we denominate dancing-dispositive and the process of de-institutionalization of insanity. Based in the philosophy of difference and in the cartographic perspective, we used the concept of dispositive in order to make visible the lines that compose it and the way they tangle in the production of different ways of subjectivation through another form of expression using the body. We followed two fortnight groups of body language recording the conversations that took place in the beginning and in the end of the activities. We also recorded our informal talks with the workshopper, with the psychiatrist responsible for the course of formation of artists of CAPS and the choreographer who was part of the artistic formation of the workshopper aiming to elucidate the body, dance and art conceptions which guided such work. Finally, we interviewed some technicians and we participated of a meeting of the team aiming to understand how that activity was perceived. We observed that the use of certain conception of dance in the field of mental health is in consonance with the the Phychiatric Reform, since it provides another way of dealing with the body, different from that produced by the contention and by the discipline. Nevertheless, we understood that there is a risk that, in some moments, the group being more a place of normalization than one of experimenting other ways of relating with yourself and with the others. We also noted that the dancing-dispositive appears as an important analyzer of the connections established at CAPS, indicating a need of the service to be more opened to the production of new care and harboring strategies, breaking the mental health facility logic of incarceration of life which still persists in the quotidian of that institution